Analisis Teknik Sinematografi Menggunakan Continuity Editing Pada Film Pendek “Batasan” - Deani Azzahra; Agusdi Syafrizal; Subhan Hartanto (JURNAL VOKASI TEKNIK, 2024)
The short film entitled "batasan" tells the story of two students who have different personalities, lazy and diligent. "batasan" film aims to convey a moral message to the community to know the limits, not to depend on and take advantage of someone's kindness. The making of the film focuses on cinematography shooting techniques and continuity editing. The use of continuity editing aims to make the audience feel comfortable and not disturbed by the unclear space or time while watching the film. This study uses the Multimedia Development Life Cycle (MDLC) method stages consisting of concept, design, material collecting, assembly, testing, and distribution. Based on the results of the questionnaire that has been distributed, respondents stated that 91% were satisfied with the film they watched, and the reliability was tested with an overall Cronbach alpha number of 0.771.